Protocol liver biopsies in stable long-term pediatric liver transplant recipients: risk or benefit?. Issue Volume 33:Issue S1(2021) (6th January 2021) - Ohlsson, Sinja; Kathemann, Simone; Pilic, Denisa; Prusinskas, Benas; Baba, Hideo Andreas; Theurer, Sarah; Dechene, Alexander; Paul, Andreas; Heinold, Andreas; Hoyer, Peter Friedrich; Lainka, Elke
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Follow-up after pediatric liver transplantation (LTX) is challenging and needs to be refined to extend graft survival as well as general functional health and patients´ quality of life. Strategies towards individual immunosuppressive therapy seem to play a key role. Our aim was to evaluate protocol liver biopsies (PLB) as a tool in personalized follow up after pediatric LTX. Patients and methods: Our retrospective analysis evaluates 92 PLB in clinically asymptomatic pediatric patients after LTX between 2009 and 2019. Histological findings were characterized using the Desmet scoring system. In addition to PLB, other follow-up tools like laboratory parameters, ultrasound imaging and transient elastography were evaluated. Risk factors for development of fibrosis or inflammation were analyzed. Results: PLB revealed a high prevalence of graft fibrosis (67.4%) and graft inflammation (47.8%). Graft inflammation was significantly ( P = 0.0353*) more frequent within the first 5 years after transplantation compared to later time points. Besides conventional ultrasound, the measurement of liver stiffness using transient elastography correlate with stage of fibrosis ( r = 0.567, P = <0.0001***). Presence of donor-specific anti-human leukocyte antigen antibodies in blood correlates with grade of inflammation in PLB ( r = 0.6040, P = 0.0018 **). None of the patients who underwent PLB suffered from intervention-related complications. Histopathological results had an impact on clinical decision making in one-third of all patients after PLB. Conclusion: PLB are a safe and useful tool to detect silent immune-mediated allograft injuries in the context of normal liver parameters.